Fictive constructions in visual space: counter-mapping colonial Singapore from 1860-1910 - Wong, Lydia Wei Ling (Nanyang Technological University, 2022)
Mainstream written narratives of Singapore from the early 20th century, such as One Hundred Years of Singapore (1921) and An Anecdotal History of Old Times in Singapore (1902), created a heavily fictionalized historical record steeped in myths, legends, and fantasies. Such fictional constructions were augmented by visual representations from colonial-era Singapore (1860– 1910): landscapes and botanical drawings; early photographic studios; and museum exhibition displays. Through close examination of such archival material from these five transformative decades, this paper examines how fantastical accounts of a place, its geographies, its peoples, and its epistemological structures were created and established as factual record in part due to widely-circulated visual representations. Furthermore, it argues that much existing scholarship and research in the region—from museum exhibitions to studies that remain heavily indebted to colonial records and archives established by a British colonial government catering to a European public—contains traces of such biases; an acknowledgement of epistemic violence within constructed visual spaces. As a counter-methodology, this study proposes to apply a Derridean-influenced process of sous rature to archival material from colonial-era Singapore in order to reveal an inherent indeterminacy within such material, which in turn offers multiple divergent narratives and new meanings. In doing so, this analytical process will begin to dismantle fictive constructions and non-factual understandings in order to “counter-map” colonial Singapore by using the same visual material previously used to construct its fantastical histories.